2010
DOI: 10.1007/s12011-010-8664-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Methionine on Toxicity of Fluoride in the Liver of Rats

Abstract: Oxidative stress is a common mechanism by which chemical toxicity can occur in the liver. The aim of the studies conducted has been to determine what influence the administration of methionine during intoxication with sodium fluoride may have upon the selected enzymes of the antioxidative system in rat liver. The experiment was carried out on Wistar FL rats (adult females) that, for 35 days, were administered distilled water, NaF, or NaF with methionine (doses: 10 mg NaF/kg bw/day, 10 mg Met/kg bw/day). The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Thus Pr supplement in the diet may not alter the serum AKP activity. As a sensitive index for liver pathological changes, SGPT activity was significantly increased in serum of rabbits treated with high F, which is coincident with results of previous investigation (Blaszczyk et al, 2011;Kanbur et al, 2009). Meanwhile, Pr or Ca supplementation significantly decreased the activity of SGPT, exerting a protective role.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Thus Pr supplement in the diet may not alter the serum AKP activity. As a sensitive index for liver pathological changes, SGPT activity was significantly increased in serum of rabbits treated with high F, which is coincident with results of previous investigation (Blaszczyk et al, 2011;Kanbur et al, 2009). Meanwhile, Pr or Ca supplementation significantly decreased the activity of SGPT, exerting a protective role.…”
Section: Discussionsupporting
confidence: 88%
“…differentially (Lu et al, 2010). In rat liver, enzymes of the antioxidative system, such as superoxide dismutase (SOD), catalase (CAT), and glutathione (GSH), were significantly inhibited after NaF exposure (Blaszczyk et al, 2011). Due to the importance of liver health for body metabolism, prevention and treatment of F-induced liver lesion have become a matter of major concern.…”
Section: Introductionmentioning
confidence: 99%
“…Together, these results show that dietary methionine deficiency induced a general mitochondrial defect in the liver of rainbow trout. At first sight, these results might seem surprising in the light of the numerous previous studies having demonstrated the antioxidant properties of methionine in several species including rainbow trout 39 44 . However, we cannot rule out the possibility of an increase of ROS production in methionine deficient condition earlier in the feeding trial that would induce the observed mitochondrial defects and the associated decrease of the oxidative status at 6 weeks.…”
Section: Discussionmentioning
confidence: 69%
“…These effects have been observed in several soft tissues and cells, such as brain [21–26], gastrocnemius muscle [26], kidney [21, 23–25, 2729], liver [19, 21, 23–25, 28, 3032], heart [21], nervous system [33], blood [5, 25, 28, 34, 35], and osteoblasts [36, 37]. …”
Section: Introductionmentioning
confidence: 99%